The Influence of E-Marketing Capability and Customer Engagement on SME Marketing Performance with Customer Trust as an Intervening Variable - Au Yong Hui Nee; Gita Sugiyarti; Aris Mardiyono (Proceeding of The International Conference on Business and Economics, 2026)
This study aims to analyze the influence of e-marketing and customer engagement on marketing performance. Analyze the influence of e-marketing and customer engagement, customer trust on marketing performance. The sample size was 78 respondents using SEM PLS for data processing. The findings of this study are that there is a significant positive influence between e-marketing on marketing performance; there is a significant positive influence between customer engagement on marketing performance; there is a significant positive influence between e-marketing on customer trust; there is a significant positive influence between customer engagement on customer trust; there is a significant positive influence between customer trust; on marketing performance